ANTI DERMATOPHYTIC ACTIVITY OF AZADIRACHTA INDICA AND ACALYPHA INDICA LEAVES- AN IN VITRO STUDY - S.M. RADHIKA,; A MICHAEL, (International Journal of Pharma and Bio Sciences, 2013)
This study was conducted to evaluate the effect of ethanolic, ethyl acetate and hexane extracts of Indian medicinal plants Azadirachta indica and Acalypha indica leaves against dermatophytes (60 isolates of Trichophyton rubrum, 22 isolates of Trichophyton mentagrophytes, 9 isolates of Microsporum gypseum and 9 isolates of Trichophyton tonsurans). Of the three extracts used the ethanolic and ethyl acetate extracts were equally good in inhibiting all the isolates. The extracts of Azadirachta indica leaves showed antifungal activity with an MIC and MFC ranging from 125µg to 500µg. On the contrary, Acalypa indica leaf extracts showed less activity with a MIC ranging from 500µg to 1000µg against all the dermatophytes tested. The minimum activity was seen with hexane at a conc of 250µg/ml for Azadirachta indica and at a concentration of 500µg/ml for Acalypha indica.